Techno-human : expedition of altered human by technology from science-fiction cinema to the post-industrial world - Caliskan, Özgür (2011)
This thesis defines techno-human as a new notion to describe altered human body and identity by technology following its expedition from the fictional world of science-fiction cinema to non-fictional world of post-industrial society. Science-fiction cinema has always significant role as an art form to define and discuss the future of interaction between human and technology.